New advances in understanding the host immune response to Pneumocystis. (December 2017) - Hoving, J Claire; Kolls, Jay K
Highlights: Trends for increased Pneumocystis jirovecii prevalence in developed countries. The type of Pneumocystis form influences the host immune response. Pneumocystis, a common colonizing organism with the potential to induce asthma. Abstract : Pneumocystis jirovecii causes clinical pneumonia in immunocompromised hosts. Despite this, the inability to cultivate this organism in vitro has likely hindered the field in ascertaining the true impact of Pneumocystis in human infection. However the recent release of the genome as well as in advances in understanding host genetics, and other risk factors for infection and robust experimental models of disease have shed new light on the impact of this fungal pathogen as to better define populations at risk. This review will highlight these recent advances as well as highlight future needed areas of research.